Islamic Marketing Ethics In The Development Of Islamic Bank Performance In Developing Countries To Increase Competitive Advantage - Riswati, Miranti; Masnita, Yolanda (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the effect of Islamic marketing ethics and convergence marketing on competitive advantage with technological capabilities as a mediating variable in Islamic banks in developing countries. The type of research used is quantitative research with questionnaire data collection techniques with likert scale measurements and the sample used was 200 respondents who have been saving and transacting for at least one year or more, and the sampling technique used was purposive sampling. The analytical tool used is the multiple linear regression (MLR). the results derived from the linear regression analysis provide insights into the relationships between Technology Capability (TC), Convergence Marketing (CM), Islamic Marketing Ethics (IME), and Competitive Advantage (CA). The findings reveal that both Technology Capability (TC) and Islamic Marketing Ethics (IME) exert a significant and positive influence on Competitive Advantage (CA), as indicated by Sig. values below 0.05 and positive coefficients. This affirms the acceptance of H1 for TC and H3 for IME. Conversely, the hypothesis H2, positing a positive and significant effect of Convergence Marketing (CM) on Competitive Advantage (CA), is rejected. The findings suggest that CM has no discernible impact on CA